Cerebellar Infarction Complicated with Acute Hydrocephalus: A Case Report - Caner F. Demir; Hasan H. Özdemir; İrem Taşcı; Metin Kaplan; Fatih Karaboğa (Türk Nöroloji Dergisi, 2012)
Acute hydrocephalus is a rare manifestation of posterior circulation strokes. A patient with cerebellar infarct and secondary obstructive hydrocephalus is described. Repeated CT showed severe third and lateral ventricular dilation suggestive for obstructive hydrocephalus. Following the shunt placement, he recovered and walks without assistance